(untitled) - Harry, Ralph Gordon (New York, 1963)
Major compilation of materials used in cosmetics as well as a number of other compounds used on the skin. The descriptions include chemical information, occurrence or manufacturing history, use in skin preparations and dermatological action
Anh văn chuyên môn - Hóa học
Keywords: Cosmetics